2016
DOI: 10.18632/aging.100949
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic degradation of yeast Fkh1 by the Anaphase Promoting Complex is required for normal longevity, genomic stability and stress resistance

Abstract: The Saccharomyces cerevisiae Forkhead Box (Fox) orthologs, Forkheads (Fkh) 1 and 2, are conserved transcription factors required for stress response, cell cycle progression and longevity. These yeast proteins play a key role in mitotic progression through activation of the ubiquitin E3 ligase Anaphase Promoting Complex (APC) via transcriptional control. Here, we used genetic and molecular analyses to demonstrate that the APC E3 activity is necessary for mitotic Fkh1 protein degradation and subsequent cell cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 59 publications
0
26
0
Order By: Relevance
“…, glucose or galactose) or defined (synthetic complete; SC) media supplemented with 30 μg/ml of all amino acids. Yeast transformations, E.coli DNA extractions, and flow cytometry were done as previously described ( Malo et al 2016 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…, glucose or galactose) or defined (synthetic complete; SC) media supplemented with 30 μg/ml of all amino acids. Yeast transformations, E.coli DNA extractions, and flow cytometry were done as previously described ( Malo et al 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…In C. elegans , it is firmly established that DAF-16, the sole FOXO ortholog in worms, is critical for normal lifespan, and lifespan extension when the insulin-signaling pathway is shut down ( Murphy and Hu 2013 ; Antebi 2013 ). It is now apparent that the yeast redundant Fox proteins Fkh1 and Fkh2 (both FKH1 and FKH2 must be deleted to observe a phenotype) are also critical for stress response and lifespan ( Zhu et al 2000 ; Shapira et al 2004 ; Postnikoff et al 2012 ; Linke et al 2013 ; Jiao et al 2015 ; Malo et al 2016 ). A third yeast Fox family member, Hcm1 , controls Fkh1 and Fkh2 transcription during G2, which regulates cell cycle progression ( Pramila et al 2006 ).…”
mentioning
confidence: 99%
“…The mRNAs encoding many APC substrates in yeast are also cell cycle regulated, with synthesis of their corresponding proteins peaking following the mRNA expression peak [75][76][77]. In fact, transcription factors that transcribe yeast APC substrates, such as Fkh1 [29] and Ndd1 [78], are targeted by the APC, thereby creating feedforward loops. This loop is further layered by the observation that the yeast Fkh2 transcription factor (also likely an APC target; our unpublished observation) recruits Ndd1 to chromatin of additional G2/M specific APC subunit promoters [79].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, accumulating evidence implicates the APC in cell cycle-independent functions such as neurogenesis, longevity, stress response and genome stability [23][24][25][26]. The idea that APC function is critical to ward off cancer is gaining traction, as the APC has been shown to be important for DNA repair decisions [27,28], to preserve genomic stability in humans and yeast [29,30], and APC impairment is associated with onset of drug resistance [31,32]. Our results, therefore, identify the APC as a potential therapeutic target that protects the genome, thereby delaying the development of aggressive treatment resistant tumors.…”
Section: Introductionmentioning
confidence: 99%
“… 23 Along these lines, a recent study has reported that Fkh1 is degraded during mitosis under stress conditions. 24 Though we have no information on how Fkh1 domain-swapping influences stress responses, one possibility is that dimerization might protect Fkh1 from degradation, thereby protecting replication initiation potential upon cell cycle entry following recovery from stress. On the other hand, degradation of Fkh1 without cell cycle arrest would potentially enable deregulated replication as in fkh1Δ cells, and while this might be expected to lengthen S phase and provoke a replication stress response, the length of S phase is not substantially altered and we have not detected replication stress resulting from FKH1 deletion or overexpression (unpublished and).…”
Section: Introductionmentioning
confidence: 99%